Lumbar multifidus characteristics and body composition in university level athletes - Anstruther, Meagan; Rizk, Amanda; Frenette, Stephane; Fortin, Maryse (Frontiers in Musculoskeletal Disorders, 2023)
Introduction Body composition is well known to affect sport performance and previous studies suggested that structural and functional lumbar multifidus (LM) impairments in athletes were associated with low back pain and lower leg injuries. However few studies have examined the relationship between LM characteristics and body composition in athletic populations. Methods This cross-sectional study included a total of 134 university varsity athletes (hockey, soccer, rugby, and football players). Ultrasound imaging was used to examined LM characteristics at the L5 bilaterally (e.g., size, thickness at rest, thickness during contraction, echo-intensity (EI) and % thickness change from rest to contraction) and body composition parameters (dual-energy Xray absorptiometry). Pearson correlations were used to assess the relationship between LM characteristics and body composition parameters. One-way ANOVA assessed differences in LM characteristics and body composition between sports. All analyses were performed separately by sex. Results LM size and thickness were positively correlated with weight, height, lean body mass and total bone mass (male: r=0.23-0.55, p<0.01-0.05; female: r=0.30-0.39, p<0.01-0.05).LM EI was strongly correlated with % body fat (male: r=0.62, female: r=0.71, p<0.01). LM thickness at rest (r=0.42, p<0.01) and contracted (r=0.27, p<0.05) were positively correlated and % thickness change was negatively correlated with % body fat in male athletes (r=-0.43, p<0.01). Discussion The significant differences in body composition and LM characteristics between sports may be attributed to sport specific demands. Understanding connections between body composition and LM may aid in preseason screening for athletes at risk of low back pain or lower leg injuries during the season.